Kinetic study on gas hydrate formation and dissociation. - Heidaryan, Ehsan (2020)
In 1884, Jacobus Henricus van\'t Hoff and Henry Louis Le Chatelier started the race for understanding chemical kinetics and equilibrium. Consequently, the scientific prowling for coming up direction, stability, and ending point of chemical reactions has not stopped. Equilibrium and kinetic of gas hydrates (also called clathrates), which are crystalline structures formed by light gas molecules (guest) enclosed by water molecules linked by hydrogen bonds, are part of this great race. Accurate knowledge of equilibrium and kinetic of gas hydrates is vital in both flow assurance of transport lines and energy production from the seabed. Traditionally, most of gas hydrates kinetic studies determine the moles of gas consumed from pressure changes measurements when the gas is getting dissolved into water to form the hydrate in an isolated system. So, in this research, a study in a standard reactor has been carried out to evaluate methane hydrate formation and dissociation at 276.2 K and various pressures of 2700, 2900 and 3200 kPa. Among many studied parameters, the second moment of the particle size distribution (µ2(t)) is the key factor to understand the properties of the produced gas hydrate even there is a wide crystal size distribution in practice, since it is related to the kinetic constant. The main objective of this dissertation is to determine methane hydrate µ2(t) based on an analytical model deduced from mass balance. In the construction of the current model, parameters of hydration number, the molar volume of gas hydrates, the initial amount of water contained in the system, and the total number of moles of reacted water are considered. The parameter of hydration number was determined by analytical analysis of quadrupole point while the molar volume of gas hydrates was calculated by using the molecular dynamics (MD) simulation technique. The initial number of moles of reacted water in current research was determined by In-situ Raman spectroscopy and results were validated against the analytical and semi-analytical rigorous model available in the open literature. The total number of moles of reacted water was calculated through a threephase flash. In the last step of the study, High Pressure micro Differential Scanning Calorimetry (HP-µDSC) has been used to better understand phase equilibrium and self-preservation phenomenon, and to determine the acting surface of methane hydrate, which is a crucial parameter in methane hydrate dissociation kinetic. Finally, a new model for methane hydrate dissociation kinetics was proposed and its validity was assessed against experimental data, showing a better agreement when compared to the conventional model approach.